Dampak Perubahan Iklim Global terhadap Keanekaragaman Hayati dan Stabilitas Ekosistem Alam : Review - I Wayan Karmana (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Global climate change has become one of the main drivers of the biodiversity crisis and the instability of natural ecosystems in various parts of the world. This study aims to systematically synthesize scientific findings related to the impact of climate change on biodiversity and ecosystem stability through a Systematic Literature Review (SLR) approach. The study was conducted on national and internationally reputable scientific articles published in the period 2010-2025, with an emphasis on the last five years. Literature searches were conducted through Google Scholar, Scopus, Web of Science, and PubMed databases using keywords related to climate change, biodiversity, and ecosystem stability. Study selection followed the PRISMA guidelines with strict inclusion and exclusion criteria to ensure the quality and relevance of the literature. The results of the synthesis indicate that climate change has a significant impact on biodiversity through shifts in species distribution, phenological disruption, habitat degradation, and increased extinction risks, especially for tropical and endemic species. This decline in biodiversity directly contributes to the weakening of ecosystem stability and resilience, both in terrestrial, freshwater, and marine ecosystems. The loss of keystone species and reduced functional redundancy have been shown to reduce the ability of ecosystems to maintain essential ecosystem functions and services, such as nutrient cycling, primary productivity, coastal protection, and climate regulation. This study confirms that biodiversity is a key foundation for ecosystem stability and that conservation efforts need to be closely integrated with climate change mitigation and adaptation strategies through an ecosystem-based approach.